The Educational Evaluation Process in the Digital Era - Călin, Iuliana (Didactica Danubiensis, 2026)
In a constantly evolving educational landscape, student assessment remains a central and sensitive component, significantly influencing both academic performance and personal development. This paper offers a comparative analysis of four major forms of assessment: traditional, modern (competency-based), inclusive, and digital. Traditional assessment, still prevalent in many education systems, is valued for its structure and objectivity but criticized for its rigidity and emphasis on rote memorization. In contrast, modern assessment focuses on key competencies and provides a more comprehensive view of student progress, encouraging active and contextualized learning. Inclusive assessment aims to ensure equity by adapting evaluation methods to the diverse needs of students, playing a crucial role in learner-centered education. Meanwhile, digital assessment introduces innovative opportunities through technology, enabling timely and personalized feedback, but also posing challenges related to accessibility and academic integrity. The study highlights the importance of a balanced, integrated, and flexible approach to contemporary assessment, aligned with the evolving demands of modern society.